The Effect of Baby Massage on the Increase in Weight of Babies Aged 3–12 Months - Salsa Farhatur Ramadhani; Widia Shofa Ilmiah; Rosyidah Alfitri (Knowledge Dynamics, 2025)
Background: Infant growth and development represent fundamental indicators of child health and well-being. Data from the 2022 Indonesian Nutrition Status Survey indicate a persistent prevalence of underweight among children, recorded at 17.0% in 2021 and slightly increasing to 17.1% in 2022. One approach commonly employed to support infant weight gain is baby massage. This study aimed to examine the effect of baby massage on weight gain in infants aged 3 to 12 months at the private midwifery practice (PMB) of Bd. Lialut Iftiyah, S.Keb, located in Malang District, Indonesia. Methods: This study employed a quasi-experimental design with a non-equivalent control group approach. A total of 36 infants aged 3 to 12 months were selected through random sampling and subsequently assigned to either the intervention group or the control group. Data were analyzed using a paired t-test. Results: The results revealed an average weight gain of 332 grams in the intervention group and 219 grams in the control group. A statistically significant difference was observed between the pretest and posttest measurements in both the intervention group (p = 0.00) and the control group (p = 0.00). Conclusion: These findings suggest that while both groups experienced weight gain, the increase was more substantial in the intervention group, indicating a greater effect of baby massage on infant weight gain.